The rainbow flag as friction : transnational imagined communities of belonging among Pakistani LGBTQ activists - Alm, Erika; Martinsson, Lena (My University, 2017)
This article analyzes the frictions the rainbow flag creates between transnational, national and translocal discourses and materialities. It focuses on the ambivalent role that the transnational ‘rainbow’ space plays for community building for LGBTQ activists in in Pakistan. The rainbow flag can function as a way to mobilize an imagined transnational community of belonging, enabling people to politicize their experiences of discrimination as a demand of recognition directed at the state. But it can also enable homonationalism and transnational middle class formations that exclude groups of people, for example illiterates and people perceived of as traditional, such as Khwaja Siras. The article is based on auto-ethnographic reflections on encounters with activists in Pakistan, and critically discusses the problem of feeling ‘too comfortable’, as white, Western, middle-class researchers, exploring ‘imperial narratives’ dominating the feminist and LGBTQ activist transnational imagined community of belonging. It argues for the importance of recognizing the transnational space as a space in its own right, with different positions, communities and conflicts stretching around the globe.
Keywords: 306 Kultur und Institutionen; rainbow flag; transnational imagined communities; LGBTQ; decolonial activism; Pakistan